Asymptotic modeling of viscoelastic thin plates and slender beams, a unifying approach - Terapabkajornded, Yotsawat; Orankitjaroen, Somsak; Licht, Christian; Weller, Thibaut (Comptes Rendus. Mécanique)
A dimension reduction problem is tackled using Trotter’s theory of convergence of semi-groups of operators acting on variable spaces [1, 2]. We show that this framework makes it possible to perform the asymptotic analysis for both viscoelastic thin plates and slender beams in a unifying manner. Several models are provided for the dynamic behavior of such structures in bilateral contact with a rigid body on a part of their boundaries with Norton or Tresca friction.